Tacit engagement in humanitarian action: making sense of silence and secrecy in humanitarian negotiations - Ayse Bala Akal; Kristina Roepstorff; Kristoffer Lidén (Journal of International Humanitarian Action)
Abstract Secrecy and silence regarding the compromises and trade-offs made by frontline humanitarians in order to achieve access, protection, efficiency and legitimacy are a widely observable but underconceptualized phenomenon in humanitarian action. As a form of “tacit engagement”, it allows humanitarian practitioners to operate in difficult settings but also implies lacking accountability, coordination and learning. There is thus a need for disentangling the productive and restraining effects of secrecy in this field. In this paper, we do so by conceptualizing these practices as forms of “tacit engagement” and relating them to political theory on secrecy and silence. Drawing on insights from expert consultations and qualitative interviews on humanitarian negotiations, we relate it to existing literatures on remote management, risk management and a culture of silence in humanitarian organizations more generally and humanitarian negotiations more specifically. In the conclusion, we work out the potentially productive and destructive effects of tacit engagement as an invitation to ethical assessment.